Digest: Population genomics reveals convergence toward melanism in different island populations. (1st June 2021) - Robert, Aloïs; Peona, Valentina; Ottenburghs, Jente
Abstract: Distinct traits between mainland and island populations provide an excellent opportunity to study the evolution and genetic basis of these traits. In this issue, Walsh et al. unraveled the evolution of black plumage color that arose independently in two island populations of the white‐winged fairywren. They also described the first steps in understanding the genetic underpinnings of this trait.